All‐Metal Oxide Transparent Photovoltaic for High‐Speed Binary UV Communication Window. (8th August 2021) - Patel, Malkeshkumar; Bhatnagar, Priyanka; Bist, Shristi; Kim, Joondong
Abstract: Optoelectronic devices that are self‐powered and have a high transparency are of interest for application in versatile next‐generation "see‐through" platforms. However, current optoelectronic photodetectors often have drawbacks including a high driving power and a relatively slow response speed. In this work, large‐area transparent photovoltaic devices (TPVD) are reported that can be easily prepared at room temperature from eco‐friendly and abundant materials. The TPVD consists of a zinc oxide/nickel oxide heterostructure as the light‐harvester and ultraviolet (UV) blocker, and its photovoltaic performance is evaluated using silver nanowire (AgNW) electrodes composed of NWs with varying diameters. As a result of surface plasmons in the AgNW electrode, TPVDs with AgNWs that have a larger diameter exhibit enhanced transparency and photovoltaic performance, with a photovoltage of 520 mV under standard AM1.5 light illumination. Importantly, the binary electric signal produced can be decoded without the need for electronic filter circuits or a threshold. A UV communication system is further designed based on the TPVD for application as a self‐powered, binary Morse‐code signal with a high response speed. This work integrates the features of a transparent power generator and transparent optoelectronics into a UV photodetector, and it can enable the application of self‐reliant devices for communications, imaging, and sensors. Abstract : This work integrates the features of the transparent power generator and transparent ultraviolet photodetector to detect high‐speed photo signals that can be received and decoded without the need for electronic filter circuits or a threshold. Such power windows enable the application of self‐reliant communications, imaging, and sensors, with no loss of vision.